Ecological integrity of agricultural properties of organic farmers in Vale do Paraíba Paulista region - Rocha, Maysa Araujo; Massi, Klécia Gili; Mendes, Tatiana Sussel Gonçalves (Paisagem e Ambiente, 2020)
Agriculture and livestock have been the main drivers of deforestation in Brazilian biomes, including Atlantic Forest, where only about 12% of its original area remains. The removal of native vegetation affects local biodiversity and ecosystem services. In this way, agroecology intends the reconciliation between biodiversity conservation, the maintenance of productivity and the capacity of the ecosystem to self-sustain. The objective of this study was to analyze the ecological integrity of seven agroecological properties in Vale do Paraíba Paulista region, through indicators of two categories (ecological factors and attributes), whose results indicated that they were in good integrity conditions. Firebreaks and forest restoration in areas without vegetation cover can contribute even more to conservation of properties.